Antennal Proteome of the Solenopsis invicta (Hymenoptera: Formicidae): Caste Differences in Olfactory Receptors and Chemosensory Support Proteins. Issue 5 (24th October 2020) - Shah, Jaee Shailesh; Renthal, Robert
Abstract: Little is known about the expression pattern of odorant and pheromone transporters, receptors, and deactivation enzymes in the antennae of ants carrying out different tasks. In order to begin filling in this information gap, we compared the proteomes of the antennae of workers and males of the red fire ant, Solenopsis invicta Buren (Hymenoptera: Formicidae). Male ants do not perform any colony work, and their only activity is to leave the nest on a mating flight. Previous studies showed that male ants express fewer types of odorant receptors than workers. Thus, we expected to find large differences between male and worker antennae for expression of receptors, transporters, and deactivators of signaling chemicals. We found that the abundance of receptors was consistent with the expected caste-specific signaling complexity, but the numbers of different antenna-specific transporters and deactivating enzymes in males and workers were similar. It is possible that some of these proteins have antenna-specific functions that are unrelated to chemosensory reception. Alternatively, the similar complexity could be a vestige of ant progenitors that had more behaviorally active males. As the reduced behavior of male ants evolved, the selection process may have favored a complex repertoire of transporters and deactivating enzymes alongside a limited repertoire of odorant receptors. Graphical Abstract: